Small but Mighty: Nanobodies in the Fight Against Infectious Diseases - Wenning Jiang; Chundong Huang; Serge Muyldermans; Lingyun Jia (Biomolecules)
Infectious diseases, caused by pathogenic microorganisms and capable of spreading, pose a significant threat to global public health. Developing efficient and cost-effective techniques for treating infectious diseases is crucial in curbing their progression and reducing patients’ morbidity and mortality. Nanobodies (Nbs), a novel class of affinity reagents derived from unique heavy chain-only antibodies in camelids, represent the smallest intact and fully functional antigen-binding fragments. Compared with conventional antibodies and their antigen binding fragments, Nbs offer numerous advantages, including high affinity, exceptional target specificity, cost-effective production, easy accessibility, and robust stability, demonstrating immense potential in infectious disease treatment. This review introduces Nbs and focuses on discussing their mechanisms and intervention strategies in the treatment of viral and bacterial infections.